The Impact of Discontinuity of the Country's Leadership in Each General Election on Country Progress and Development: A Multifaceted Analysis - Mujuranto Sihotang; Bliese Vloeberghs Gilpin; Siemer Kolshus; Platts Glover Jaffe; Inglehart Heifetz (Intitute of Computer Science (IOCS), 2022)
This research delves into the intricate relationship between interrupted presidential leadership and a country's progress and development. By examining a diverse range of factors including the nature of interruption, institutional strength, political polarization, public sentiment, and leadership continuity, this study presents a nuanced understanding of the multifaceted impacts that interrupted leadership can generate. Through a synthesis of existing literature, comparative case studies, and in-depth analyses, this research reveals that the outcomes of interrupted leadership are far from uniform. Positive impacts can arise from well-managed transitions, transparent succession plans, and alignment with national interests. Conversely, abrupt changes, weak institutions, and political divisions can magnify negative consequences. The research underscores the vital role of effective governance, transparent transitions, and policy continuity planning in mitigating adverse impacts. Furthermore, it emphasizes the need for tailored strategies in diverse contexts to harness the potential benefits and mitigate the challenges posed by interrupted presidential leadership. The implications of this research extend to policymakers, scholars, and citizens alike, guiding informed decisions, enriching academic discussions, and fostering active engagement in the governance processes that shape a nation's trajectory.